Evaluation of Fatigue Tests by Means of Mathematical Statistics - Sivák, Peter; Ostertagová, Eva (Procedia engineering, 2012)
Wöhler curve is the most frequently used S-N curve in life calculations and in determination of fatigue damage accumulation in components of supporting structures. The curve can solely be derived from long-term fatigue tests with constant stress amplitude by means of Experimental Stress Analysis (EAN). Fatigue tests are performed using special testing devices while the whole testing process follows relevant regulations. The set of data gained by measurements undergoes further processing and evaluation by means of mathematical statistics using relevant application software. This paper presents an example of a statistical evaluation of a data set obtained from fatigue tests of construction steel KONOX 345T. The paper further includes theoretical foundations for calculation and application of a simple linear regression model. In the applications the model is fitted to relevant data using the method of least squares. For quality measurements of the regression model we used two error measures – root mean squared error and coefficient of determination.